Electrochemistry of Ru(edta) complexes relevant to small molecule transformations: Catalytic implications and challenges - Chatterjee, Debabrata; Oszajca, Maria; Katafias, Anna; van Eldik, Rudi (Coordination Chemistry Reviews, 2021)
Electrochemistry of Ru(edta) complexes (edta4− = ethylenediaminetetraacetate) progressed over a period of several decades, with significant increase in understanding of the electro-catalytic processes involving the substrate coordinated to the metal center. While electrochemistry studies of many Ru(edta) complexes were published in several papers, no attempt has been made to provide a comprehensive and systematic overview of its electrochemical properties, evaluating its application to catalytic electrochemical transformation of small molecules. In this article, results of the electrochemical studies of both mononuclear and binuclear complexes of Ru(edta) are reviewed with regard to electron-transfer reaction mechanism and activity. Their potential to act as redox mediators or catalysts in electrochemical transformations of small molecules and enzymatic reactions, are highlighted. This review aims to contribute to the mechanistic understanding of Ru(edta) complexes in catalysis of such electrochemical transformations.
CRIS-Team Scopus Importer:2021-03-19
Keywords: Binuclear complexes; Electrochemistry; Mononuclear complexes; Ru(edta); Small molecule activation